Case Report: Durable disease stability in a patient with MET exon 14 skipping mutation and brain metastasis NSCLC following radiotherapy and immunotherapy - Ma, Ji; Zhang, Depeng; Cui, Yang; Meng, Dongfang; Wei, Zhigang; Ye, Xin (Frontiers in Immunology, 2026)
BackgroundNon-small cell lung cancer (NSCLC) with brain metastasis (BM) is associated with poor prognosis. For those patients with MET exon 14 skipping mutation (METex14), although MET tyrosine kinase inhibitors (MET TKIs) have emerged, but their efficacy remains limited, with the median progression-free survival (PFS) no more than 14 months. Herein, we present a case of a NSCLC patient with BM and METex14, who achieved prolonged PFS of 41 months following brain radiotherapy initiation and camrelizumab (a PD-1 inhibitor).Case presentationA 75-year-old man was diagnosed with lung adenocarcinoma with BM and METex14. He received 7 months of crizotinib as first-line therapy, after that, the lung and brain lesions enlarged. Then, programmed cell death-ligand 1 (PD-L1) showed the tumor proportion score (TPS) approximately 80%, he underwent brain radiotherapy combined with camrelizumab immunotherapy. After treatment, the lesions in the patient’s lung and brain were significantly reduced. Camrelizumab maintenance therapy was continued for 20 months until the appearance of pulmonary aspergillosis, with the patient achieving a PFS of 41 months.ConclusionThe combination of brain radiotherapy and camrelizumab demonstrated efficacy in a lung adenocarcinoma patient with BM and METex14. These findings suggest that immunotherapy may represent a potential treatment approach for high PD-L1 expression of METex14 NSCLC patients, warranting further investigation in larger cohorts.